INTEGRASI NILAI-NILAI SPIRITUAL SUKU BADUY KE DALAM PEMBELAJARAN SEKOLAH DASAR - Amelia Yustina Fatmawati; Ryco Hermawan; Enong Holilah; Ila Rosmilawati; Ujang Jamaludin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study investigates how the spiritual values embedded in the Baduy community can be meaningfully incorporated into elementary school learning as a strategic approach to strengthening character education and enhancing cultural relevance in classroom practices. The central issue addressed is the limited integration of local wisdom particularly core Baduy values such as pikukuh, simplicity, ecological harmony, and adherence to customary regulations into instructional materials, despite their strong potential to support holistic character development. The primary objective of this research is to identify the fundamental spiritual principles of the Baduy people and articulate pedagogical pathways for embedding these values into elementary education. Employing a qualitative descriptive approach, the study draws upon extensive literature reviews, ethnographic documentation, and community-based sources reported in earlier scholarly work. The findings demonstrate that Baduy spiritual values can enrich instructional processes through contextually grounded thematic learning, the incorporation of ethnoscience perspectives, and the cultivation of multicultural awareness among young learners. The study further reveals that integrating these cultural values encourages environmentally responsible attitudes, reinforces discipline, and nurtures students’ cultural sensitivity. Moreover, the results highlight that effective integration demands coordinated efforts among teachers, community leaders, and curriculum designers to ensure sustainability and cultural accuracy. Overall, the research underscores that the spiritual heritage of the Baduy community offers substantive contributions to character-driven and culturally responsive elementary education.